Molecular Detection of Jembrana Disease in Balinese Cattle (Bos sondaicus) Samples at the Lampung Veterinary Center - Kurniasih, Vidyanti; Rustiati, Elly Lestari; Srihanto, Eko Agus; Firwantoni, Firwantoni; Heni, Ahyul; Panasea Anggy, Fransiska; Febriyani, Dwi Ayu (Jurnal Agrosci, 2025)
Jembrana Disease is an infectious disease in Balinese cattle, which is characterized by fever and inflammation of the oral mucous membranes (stomatitis, enlarged lymph nodes of the preskapularis, prefemolaric, and parotid, sometimes accompanied by blood sweating. This disease reaches a mortality rate of no more than 20% caused by the Jembrana Disease Virus (JDV). According to data from the Directorate of Animal Health, Jembraa Disease cases continue to increase from year to year, with as many as 398 cases in 2016 and increased to 4,797 cases in 2018. The presence of the Jembrana virus can be detected through tests. One of them is by identifying and isolating the pathogen. Technological breakthroughs in DNA-based testing systems are becoming an available alternative. Viruses can be detected through commonly used molecular analysis such as Polymerase Chain reaction (PCR). The Jembrana Disease test was carried out at the Biotechnology Laboratory of the Lampung Veterinary Center using PCR and then visualized by agarose gel electrophoresis. The test results of 53 samples consisting of 50 types of buffycoat samples and 3 types of organ samples showed that 1 type of organ sample was detected with JDV